THE UTILIZATION OF ALVARADO, AIR AND RIPASA SCORING SYSTEMS IN ADULTS WITH ACUTE APPENDICITIS TREATED WITH LAPAROSCOPIC APPENDECTOMY - Milev, Ilija; Velikj Stefanovska, Vesna; Kostovski, Ognen; Mitevski, Aleksandar; Karagjozov, Panche; Petrovski, Stefan (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
The purpose of this study is to evaluate the applicability of Alvarado, Appendicitis Inflammatory Response (AIR) and â€žRaja Isteri Pengiran Anak Saleha Appendicitis â€œ(RIPASA) score in diagnosing acute appendicitis (AA) in our population, as well as the possibility for connection between certain values and the emergence of â€œadverse eventsâ€ in relation to laparoscopic appendectomy (LA). We conducted a multicentric, prospective, cohort, clinical study on 75 patients with AA treated with LA. For all the patients, the values and corresponding group of the three scoring systems (Alvarado, AIR and RIPASA) were determined preoperatively. We registered the emergence of intraoperative complications and difficulties, reason for conversion and the presence of complications postoperatively. All the patients with some form of intraoperative complication or difficulties, patients on whom conversion to open approach was performed or patients with any kind of postoperative complication were placed in the group â€œwith adverse eventsâ€ and the rest in the group â€œwithout adverse eventsâ€. The RIPASA score had an insignificantly higher sensitivity (sens.=96% at a cut-off Ëƒ7 and  sens.=68% at a cut-off Ëƒ12) than Alvarado score (sens.=90.7% at a cut-off â‰¥7 and sens.=62.7% at a cut-off â‰¥9) and both had significantly higher sensitivity than AIR score (sens.=40% at a cut-off â‰¥9). Further analysis showed that there was no association between the emergence of adverse events and the corresponding group of the scoring system. The RIPASA scoring system had the highest sensitivity in our population, The investigated scoring systems Alvarado, AIR and RIPASA could not be used for predicting possible unwanted course in patients with AA treated with LA. Keywords: scoring systems, sensitivity, laparoscopic appendectomy, adverse events.